Pertimbangan Fungsional dalam Penentuan Lakon dan Keputusan Pementasan Wayang Topeng Malang - Hidajat, Robby; Wiflihani, Wiflihani; Razak, Amir (Mahesa Research Center, 2025)
This study aims to identify and analyze the functional considerations underlying the community's decision to organize a Wayang Topeng Malang performance by selecting a particular play. Given the high costs associated with staging this performance, the decision-making process has a significant impact on the supporting community. The study uses a functional method, and data is collected through in-depth interviews, observations, and literature reviews (books, scientific articles, and mass media publications). Data analysis is carried out through tabulation and interpretation based on the tendency of the function to organize performance. The results of the study indicate that the decision to stage a Wayang Topeng Malang performance is influenced by three main categories of considerations: (1) Consideration of the Purpose of the Performance (for example, for traditional ceremonies or entertainment), (2) Consideration of Interests (both individual and social), and (3) Consideration of the Expectations desired from the performance. These findings confirm that the determination of the play and the decision to perform the Wayang Topeng Malang performance is a phenomenon driven by clear social and cultural functions in the lives of the Malang community.